A review on the recycling of spent garnet as a mixing ingredient in concrete - Sofia Adibah, Jasni; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar; Shahrul Niza, Mokhatar; Ismail, Mohamed A. (Semarak Ilmu Publishing, 2025)
Construction industry has increased rapidly leading to increase in concrete usage. This contributes to its limitation of natural resources and issue of sand shortage in certain place. This problem primarily due to the uncontrolled river sand mining. The demand for eco-friendly construction methods has driven research into substitute materials for conventional sand, and aggregates. Thus, embracing industrial by-products known as spent garnet as alternative materials presents an appealing solution to mitigate reliance on sand resources, thereby contributing to the sustainability of river ecosystems. Spent garnet is a waste derived from the surface treatment process in the shipping industry and is usually dumped in landfills. This review critically examines the viability of integrating spent garnet into construction materials. Comprehensive assessments of the physical and mechanical properties of these composite materials shed light on the potential improvements and challenges associated with the use of spent garnet. Ultimately, the review synthesizes the current state of knowledge on spent garnet in construction, offering valuable insights for researchers and industry professionals seeking innovative, sustainable solutions in materials science and waste management.